2008
DOI: 10.1089/ten.tea.2007.0048
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Tissue Regeneration with Adipose-Derived Stem Cells

Abstract: A number of surgical techniques have been developed to promote periodontal tissue regeneration. Bone marrow-derived stem cells have also been shown to promote periodontal tissue regeneration. In this study, we sought to determine whether adipose-derived stem cells (ASCs) can promote periodontal tissue regeneration as well. ASCs were isolated from a Wistar rat, passaged twice, mixed with platelet-rich plasma (PRP) obtained from inbred rats, and implanted into the periodontal tissue defect that had been generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 36 publications
2
137
1
3
Order By: Relevance
“…We have previously reported the extraordinary multipotency inherent in murine ASCs with respect to their ability to undergo chondrogenic, 11 osteogenic, 11 adipogenic, 12 and neurogenic 13 differentiation of mouse ASCs in vitro. We have also demonstrated in vivo adipose tissue regeneration 14 using mouse ASCs and in vivo periodontal tissue regeneration 15 using rat ASCs. Some reports suggest that ASCs, unlike with bone marrowderived mesenchymal stem cells (MSCs), are not suitable for cartilage regeneration.…”
mentioning
confidence: 78%
“…We have previously reported the extraordinary multipotency inherent in murine ASCs with respect to their ability to undergo chondrogenic, 11 osteogenic, 11 adipogenic, 12 and neurogenic 13 differentiation of mouse ASCs in vitro. We have also demonstrated in vivo adipose tissue regeneration 14 using mouse ASCs and in vivo periodontal tissue regeneration 15 using rat ASCs. Some reports suggest that ASCs, unlike with bone marrowderived mesenchymal stem cells (MSCs), are not suitable for cartilage regeneration.…”
mentioning
confidence: 78%
“…Human ASCs in vitro [19] Human ASCs in athymic nude rats [39] Chondrogenic differentiation Human ASCs in vitro [56,57,91,92] Human ASCs in SCID mice [54] Osteogenic differentiation Human ASCs in vitro [93][94][95][96] Human ASCs in nude mice [97] Human ASCs in SCID mice [19,98] Human ASCs in athymic mice [45] Human ASCs in rats [75] Rat ASCs in SD rats [40] Myogenic differantiation Human ASCs in vitro [60,[99][100][101] Human ASCs in mdx mice [102] Human ASCs in nude mice [34] Cardiomyogenic differentiation Human ASCs in vitro [103,104] Rat ASCs in rats [105] Neuronal differentiation Human ASCs in vitro [43,106] Canine ASCs in dogs with spinal cord injuries [107] Rat ASCs in rats [70] Osteogenic constructs with intrinsic vascularization Human ASCs in nude mice [66,69] Epithelial differentiation Human ASCS in vitro [59,74] Kidney differentiation Human ASCs in C57BL/6 mice [108] Pancreatic differentiation Human ASCs in vitro [72,73] Hepatocyte differentiation Human ASCs in Pfp/Rag2 knockout mice [77] Human ASCs in Ccl4 mice [76] Periodontal tissue regeneration Rat ASCs in rats [109] The proposed uses for ASCs in tissue engineering and regenerative medicine are collected in Tab. 1.…”
Section: Neuronal Differentiationmentioning
confidence: 99%
“…In this context, a potential tissueengineering approach to periodontal and bone regeneration involves the incorporation of progenitor cells and instructive messages in a prefabricated three-dimensional construct and subsequent implantation of the construct into the defect site [37]. Several studies have shown that autologous bone marrow mesenchymal stem cells can regenerate alveolar bone and periodontal ligament-like structures after transplantation in vivo [9,41,42]. The use of LLLI on these biomaterials before transplantation could lead to a faster and greater regeneration.…”
Section: Discussionmentioning
confidence: 99%